ANTIBIOTIC THERAPY FAILURE AND THE RISING CHALLENGE OF ANTIMICROBIAL RESISTANCE IN PEDIATRIC PNEUMONIA PATIENTS IN KHYBER PAKHTUNKHWA PAKISTAN - Muhammad Esa; Rabia Iqbal; Irfan Hamid; Kashif Sohail; Zeeshan Javaid; Zul Kamal; Asad Ur Rahman; Muhammad Abbas Amanat; Kashif Ali Khan; Bashir Ullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Drug-resistant bacterial strains cause various infections including pneumonia, which then go unchecked, as the prevalence of culture and sensitivity tests are not entertained before planning therapy. The current study aimed to evaluate the prescribing practices of antibiotics, therapy failure, and to assess the patient response. Therapy failure and antibiotic switching-over are a sign of drug-resistance and possibly antimicrobial resistance (AMR). Methods: A total of n=60 pediatric pneumonia cases were collected and evaluated for prescription pattern of antibiotics, hospital longevity, overall antibiotic consumption, switching-over and patient discharge assessment, respectively. Results: The study results showed that pneumonia is more common in children (1-5 years); n=24 (40%), followed by neonates (0-12 months); n= 19 (31.6%), respectively. Monotherapy was used upon initial admission of patients, while combination therapy and antibiotic switching-over were noticed when patients were not responding to initial antibiotic therapy. Due to non-responsiveness, the patient’s hospital stay was prolonged and antibiotic regimens were switched over indicating the possibility of drug-resistant bacterial strains. Next, upon utilization of monotherapy (single antibiotic), the average hospital stay was 6.5 days, while 3.5 days with combination therapy (two antibiotics). The total number of antibiotics were 122 with highest number prescriptions of cefoperazone (n=35, 28.6%), meropenem (n=31, 25.4%), and vancomycin and linezolid both having n=24 (19.6%) for each. The most commonly used regimens were meropenem+linezolid (n=9), meropenem+vancomycin (n=7) followed by cefoperazone+linezolid and cefoperazone+vancomycin both having n=5, respectively. Switching-over was noted mostly for monotherapy drugs cefoperazone (15 times), followed by ampicillin, ceftriaxone and meropenem (2 times), respectively. Furthermore, meropenem+linezolid reflected as the best combination with patient discharge n=10 with 16.6% and hospital longevity less than 2 days. Conclusion: This study highlights the emerging silent pandemic of drug-resistant bacterial strains responsible for causing pneumonia in pediatric patients. This trend may be perceived as a sign of AMR, and needs careful watch and reporting. We recommend further studies on provincial and national level hospitals to prevent the upcoming health concern and its worse consequences.